The Civil Responsibility of Tourist Gazebo Owners in the Kurdistan Region - Rdhwan Shareef Salih; Helin Abdulrahman Towfiq (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Humans are responsible for how they treat the goods and things that are under their care or control, and in the event of any damage caused by them, civil liability arises and the sufferer must be compensated. Tourist gazeboes, which are currently very common in tourist areas of the Kurdistan Region, are not excluded from harming tourists and frequently caused various accidents in tourist attractions, even resulting in tourist deaths. Although the responsibility of the owners of tourist gazebos is not regulated by a specific law or article, in the event of any damage, according to the general provisions of the Iraqi Civil Law and regulations, it will be decided. Therefore, the main purpose of this study is to determine the type of responsibility of the tourist gazebo’s owners and the legal adaptation of this responsibility, as well as present the conditions and legal basis of this responsibility. To achieve this goal, this study follows an analytical and comparative method that analyzes the relevant articles of the Iraqi Civil Law in force in the Kurdistan Region and compares them with the Egyptian and Jordanian Civil Laws. Finally, we concluded that the liability of the tourist gazebo’s owners can be contractual and also can be tort in the type of building responsibility, and a number of conditions must be met for the responsibility to arise. It is also proposed that this responsibility be more specifically regulated legally.